COMMISSIONERS METHOD FOR LAST SURVIVOR WHOLE LIFE INSURANCE RESERVES WITH GOMPERTZ LAW - Hidayat, Agus Sofian Eka; Styven, Arnol (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Life insurance plays an important role in protecting one’s life in terms of financial risks. The right required reserve is one aspect that should be secured to obtain a good company’s financial health. A study reported that insufficient reserve is one of the primary causes of insolvency issues among bankrupted insurance companies. Therefore, this study aims to use the Commissioners method in calculating the reserve of the last-survivor whole life insurance policy The Gompertz mortality law is used to estimate Indonesian death probability of age . Gompertz law is employed due to its practical convenience in dealing with continuous case calculation. Linear Least Square Method will be utilized to estimate the Gompertz parameters and . This study uses secondary data from Indonesian Mortality Table IV published by OJK. The result of this study is that the reserve of multiple life status policies, such as last-survivor insurance, depends on the states of individuals of each pair. In this study, the reserve has the highest amount in cases where only the male person is alive. Average Relative Error values of the estimated Gompertz to the TMI IV show that the overall accuracy exhibits a deviation of up to 1.67%. MAPE values of Gompertz show that the estimated model best fits the TMI IV for the interval age of 0-60.